2011
DOI: 10.1371/journal.pgen.1002304
|View full text |Cite
|
Sign up to set email alerts
|

A One Base Pair Deletion in the Canine ATP13A2 Gene Causes Exon Skipping and Late-Onset Neuronal Ceroid Lipofuscinosis in the Tibetan Terrier

Abstract: Neuronal ceroid lipofuscinosis (NCL) is a progressive neurodegenerative disease characterized by brain and retinal atrophy and the intracellular accumulation of autofluorescent lysosomal storage bodies resembling lipofuscin in neurons and other cells. Tibetan terriers show a late-onset lethal form of NCL manifesting first visible signs at 5–7 years of age. Genome-wide association analyses for 12 Tibetan-terrier-NCL-cases and 7 Tibetan-terrier controls using the 127K canine Affymetrix SNP chip and mixed model a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 28 publications
(23 reference statements)
0
48
0
Order By: Relevance
“…We obtained blood anti-coagulated with EDTA from 18 members of the Golden Retriever family including the common grandmother, the [18,19] † There are as yet no known canine models for CLN3, CLN4, CLN11, CLN13 or CLN14; CLN9 is not in current use. ‡ A canine lysosomal storage disease originally described as a NCL [20] is more appropriately classified as a mucopolysaccharidosis [21,22].…”
Section: Subject Dogsmentioning
confidence: 99%
See 2 more Smart Citations
“…We obtained blood anti-coagulated with EDTA from 18 members of the Golden Retriever family including the common grandmother, the [18,19] † There are as yet no known canine models for CLN3, CLN4, CLN11, CLN13 or CLN14; CLN9 is not in current use. ‡ A canine lysosomal storage disease originally described as a NCL [20] is more appropriately classified as a mucopolysaccharidosis [21,22].…”
Section: Subject Dogsmentioning
confidence: 99%
“…Among the animal species, NCLs have most frequently been reported in dogs. Previous studies have identified 9 different mutations in the canine orthologs of 8 of the 13 genes associated with human NCL as shown in Table 1 [10][11][12][13][14][15][16][17][18][19][20][21][22]. Prior to the discovery of the causative mutations, NCL was common in three dog breeds: the Tibetan Terrier, the Border Collie, and the American Bulldog [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ATP13A2 mutations have been shown to cause a late onset neurodegenerative phenotype in dogs [79]. ATP13A2 encodes a lysosomal divalent cation transporter [80].…”
Section: Pathogenesismentioning
confidence: 99%
“…A similar link between NCL and Kufor-Rakeb disease was established when ATP13A2 mutations were recently identified in Tibetean terriers with NCL [147,148]. In this context it is interesting that some patients with NCL have parkinsonism and that brains of NCL patients caused by Cathepsin D deficiency (CLN10) show intense alphasynuclein staining [144].…”
Section: Kufor-rakeb Disease (Park9)mentioning
confidence: 65%